Makna Pesan Sosial dalam Iklan Layanan Masyarakat “Stereotip Z”: Sebuah Kajian Semiotika Riffaterre - Budi Santoso; Andi Halang Lewa (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
Abstract Public Service Advertisements are non-commercial advertisements that aim to sell ideas for the benefit of public service. The message of Public Service Advertisements contains suggestions and persuation  to the public to take an action that changes their "bad" behavior for the better behavior . This paper attempts to describe the meaning of social messages in the text of public service advertisements “Stereotype Z”. Data analysts use  Riffaterre’s semiotic approach. Through heuristic and hermenetic reading, analysis of the indirect expressions, matrix, model, variant, and hypogra, results show that the text of public service advertisements "Stereotype Z” contains  a social  message that persuade the young generation (generation Z) to be more critical about the problems in their suroundings.